Optimal Nitrogen Accumulation and Remobilization Can Synergistically Improve Maize Yield and Nitrogen-Use Efficiency Under Low-Nitrogen Conditions - Xiang Li; Lin Piao; Wenhao Duan; Yan Bai; Nanheng Zhu; Qingquan Tang; Fangming He; Hong Ren; Yan Gu (Agronomy)
Increasing the nitrogen (N) use efficiency (NUE) of modern high-yield maize hybrids is essential for food security and reducing environmental risks. However, the relationship between dry matter (DM), N accumulation, and reallocation among different high-yield maize hybrids and NUE, particularly under various N fertilization levels, is not well understood. The field experiment was conducted in Jilin Province, Northeast China. In this study, two maize hybrids, Zhengdan958 (ZD958) and Tie 391 (T391), were grown under four N fertilizer levels: 0 (NN), 120 (LN), 240 (MN), and 360 (HN) kg ha−1. We examined the effects of N input on grain yield, NUE, DM, and N accumulation, partitioning, and reallocation of these two high-yielding maize hybrids during the 2023–2024 growing season. The results showed that N input significantly increased grain yield but reduced NUE. There was no significant difference in yield and NUE between the two maize hybrids at the HN level. However, under LN conditions, the grain yield and NUE of ZD958 were higher by 16.2% and 15.6%, respectively, compared to T391. Meanwhile, ZD958 exhibited greater per-silking and post-silking DM (5.0% and 7.9%) and N accumulation (11.6% and 32.7%), as well as a higher amount of reallocated DM (45.6%) and N (17.5%) compared to T391. Moreover, 15.5–38.1% of grain N for ZD958 and 17.2–46.7% for T391 still needed to be reallocated from vegetative organs, with a larger fraction coming from the stem rather than the leaves. The middle leaves and lower stems of the canopy tended to reallocate more N to the grain, and lower-layer stem N reallocation was significantly related to grain yield. In conclusion, higher accumulation of DM and N, along with greater N reallocation—especially from the lower-layer stem—could be regarded as important traits in maize breeding to improve the NUE of high-yield maize hybrids under insufficient N supply.